Work Engagement Tenaga Kesehatan Gigi: Studi Kasus di Poli Gigi RS X - Salsabila, Arini Isyfa; Chusniyah, Tutut (Flourishing Journal, 2025)
The work engagement of health workers, including dental health workers, is an important factor in maintaining the quality of service, but research shows that the level is still low due to high work demands and limited resources. This study aims to describe the level of work engagement of dental health workers at Hospital X and identify factors that influence the level of work sustainability. The results showed that social support from coworkers, physical comfort in the workplace, and a supportive work environment played a significant role in increasing the work tenure of dental health workers. However, challenges such as work stress, high workload, and interactions with uncooperative patients remain barriers to maintaining work. These findings support the Job Demands-Resources (JD-R) theory, which emphasizes the importance of a balance between job demands and job resources in maintaining work. This study suggests the need for systematic efforts to manage stress and improve social support and working conditions in order to improve the work level and well-being of dental health workers. AbstrakKeterlibatan kerja tenaga kesehatan, termasuk tenaga kesehatan gigi, merupakan faktor krusial dalam menjaga kualitas pelayanan, namun studi menunjukkan tingkatnya masih rendah akibat tuntutan kerja tinggi dan sumber daya terbatas. Penelitian ini bertujuan untuk menggambarkan tingkat work engagement tenaga kesehatan gigi di RS X serta mengidentifikasi faktor-faktor yang memengaruhi tingkat keterikatan kerja tersebut. Hasil penelitian menunjukkan bahwa dukungan sosial dari rekan kerja, kenyamanan fisik di tempat kerja, dan lingkungan kerja yang mendukung berperan signifikan dalam meningkatkan keterikatan kerja tenaga kesehatan gigi. Meskipun demikian, tantangan seperti stres kerja, beban kerja yang tinggi, serta interaksi dengan pasien yang tidak kooperatif tetap menjadi hambatan dalam mempertahankan keterikatan kerja. Temuan ini mendukung teori Job Demands-Resources (JD-R), yang menekankan pentingnya keseimbangan antara tuntutan pekerjaan dan sumber daya kerja dalam memelihara keterikatan kerja. Penelitian ini menyarankan perlunya upaya sistematis untuk mengelola stres dan meningkatkan dukungan sosial serta kondisi kerja guna meningkatkan tingkat keterikatan kerja dan kesejahteraan tenaga kesehatan gigi.